2016
DOI: 10.1186/s12873-016-0094-1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among head trauma patients taking preinjury antithrombotic agents: a retrospective cohort analysis from a Level 1 trauma centre

Abstract: BackgroundBleeding represents the most well-known and the most feared complications caused by the use of antithrombotic agents. There is, however, limited documentation whether pre-injury use of antithrombotic agents affects outcome after head trauma. The aim of this study was to define the relationship between the use of preinjury antithrombotic agents and mortality among elderly people sustaining blunt head trauma.MethodsA retrospective cohort analysis was performed on the hospital based trauma registry at O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Multiple studies have been unable to demonstrate a consistent benefit with or without TEG guidance. [11][12][13][14][15][16] We have confirmed, as reported by previous studies, that there was no increase in patient safety complications among patients who did not receive antiplatelet therapy reversal. We have further demonstrated that platelet transfusions do not prevent the need for invasive neurosurgical interventions including ICP monitoring, burr holes, and craniotomy for TICH extension in blunt TBI patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Multiple studies have been unable to demonstrate a consistent benefit with or without TEG guidance. [11][12][13][14][15][16] We have confirmed, as reported by previous studies, that there was no increase in patient safety complications among patients who did not receive antiplatelet therapy reversal. We have further demonstrated that platelet transfusions do not prevent the need for invasive neurosurgical interventions including ICP monitoring, burr holes, and craniotomy for TICH extension in blunt TBI patients.…”
Section: Discussionsupporting
confidence: 87%
“…10 Multiple studies, however, have been unable to demonstrate a consistent benefit to platelet transfusion in this patient population. [11][12][13][14][15][16] A recent large trial utilizing thromboelastography with platelet mapping (TEG-PM) to direct the decision for platelet transfusion to reverse platelet dysfunction similarly demonstrated no improvement in clinical outcomes. 17 We sought to determine whether emergent platelet transfusion reduces the incidence of hemorrhage expansion, mortality, or need for neurosurgical intervention such as intracranial pressure (ICP) monitoring, burr holes, or craniotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a pre-injury ASA-PS score of ≥ 3 were substantial (28%) compared to CENTER-TBI which was 11% (Steyerberg et al 2019); the latter is similar to the general trauma population admitted to OUH (10%) (Sovik et al 2014). The more silent comorbidity; antithrombotics, were used by 42% of our TBI patients > 50 years and this compares to other TBI studies, 33-47%, on the elderly population (Gaist et al 2017;Julien et al 2017;Narum et al 2016;Lenell et al 2019). In the total Norwegian population 18% ≥ 40 years use antithrombotic drugs (Berg et al 2017) in line with previously mentioned EU study (Steyerberg et al 2019).…”
Section: Discussionmentioning
confidence: 54%
“…In patients with blunt head trauma, a previous meta-analysis of case-control and cohort studies showed only a slight and non-significant increased risk of death in patients who were taking pre-injury APA [ 790 ]. Further studies found both an association with worsening of the lesion [ 791 , 792 ], need for neurosurgical intervention [ 791 ], prolonged hospital stay and increased rate of disability [ 793 ], or no influence on survival [ 794 , 795 ], neurological outcome [ 786 , 796 ], need for neurosurgical intervention [ 794 , 797 ], haemorrhagic complications and need of re-operation after decompressive craniectomy [ 798 ], questioning the need for routine neurosurgical consultation [ 797 ] or repeat CT [ 799 ] in cases of mild head trauma or low-altitude falls in patients treated with APA (mainly aspirin, clopidogrel or both).…”
Section: Resultsmentioning
confidence: 99%